(untitled) (International Journal of Architecture and Urbanism, 2020)
Ulos is a well known cultural heritage, but as technology advances, the production of traditionally weaved Ulos began to be left behind, when in fact, the traditionally weaved Ulos held a very high artistic value and in need of preservation. Tarutung is an area with the potential to be developed as a tourist city with a variety of nature and culture, such as the Ulos craft, which is a valuable asset. Every year the Festival Tenun Nusantara is held in Tarutung that can support the design of the Ulos weaving center. That is why an Ulos center is needed. The methodology of this Ulos weaving center starts by conducting site selection, identifying problems and potential that exist on the site, then collecting data that support the design by searching ideas, literature studies related to titles and themes, observation studies, and comparative studies. The Ulos weaving center uses the neo vernacular architecture theme by incorporating local wisdom and natural surroundings of the site, a rice field that becomes an innovative attraction. Therefore, Ulos weaving center allows people to get to know Ulos deeply in a whole new experience and a place suitable to enrich and conserve cultural tradition in Tarutung.